2022
DOI: 10.1186/s12014-022-09345-1
|View full text |Cite
|
Sign up to set email alerts
|

Data-independent acquisition mass spectrometry in severe rheumatic heart disease (RHD) identifies a proteomic signature showing ongoing inflammation and effectively classifying RHD cases

Abstract: Background Rheumatic heart disease (RHD) remains a major source of morbidity and mortality in developing countries. A deeper insight into the pathogenetic mechanisms underlying RHD could provide opportunities for drug repurposing, guide recommendations for secondary penicillin prophylaxis, and/or inform development of near-patient diagnostics. Methods We performed quantitative proteomics using Sequential Windowed Acquisition of All Theoretical Frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 59 publications
0
5
0
2
Order By: Relevance
“…For the proteomic workflow, extraction and processing followed the method described in Salie et al [ 45 ]. Briefly, SWATH-MS data files were searched using openSWATH (version 2.0.0) against a published plasma spectral library [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…For the proteomic workflow, extraction and processing followed the method described in Salie et al [ 45 ]. Briefly, SWATH-MS data files were searched using openSWATH (version 2.0.0) against a published plasma spectral library [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…This method compares the importance of the real predictor variables with those of permuted copies of the original features through statistical testing and multiple iterations of random forests. Boruta Feature selection has been applied to SWATH-MS data in various studies [ 15 , 16 ] and has been shown to be effective and a most stable methodology in permutation-based feature selection [ 17 ]. To rank feature importance, the Boruta algorithm employs mean Z-scores, indicating the number of standard deviations a data point deviates from the mean.…”
Section: Methodsmentioning
confidence: 99%
“…В исследованиях последнего десятилетия подчеркивается роль генетической предрасположенности в развитии РБС [6]. Исследователями установлен ряд генов-кандидатов, которые ассоциированы с предрасположенностью к развитию данной патологии [6][7][8]. Однако следует отметить, что имеющиеся на сегодняшний день результаты противоречивы, а также имеют ряд ограничений, которые касаются размера выборки (в среднем в исследования включаются не более 100 пациентов).…”
Section: ключевые моменты Key Messagesunclassified
“…В ранее проведённом исследовании мы установили, что генотипы генов IL1RA и IL4 являются рис- Исследования непосредственно иссечённых клапанов сердца при хирургическом вмешательстве демонстрируют, что клапанные структуры характеризуются повышенным уровнем фактора некроза опухоли (TNF-α), интерферона гамма (INF-γ), а также низким уровнем интерлейкина 4 [4]. Современные методы исследований, такие как массспектрометрия, определяющая протеомный профиль образцов, позволили выявить ряд белковых маркеров (адипонектин, компонент комплемента с7, фибу-лин-1, фиколин 3 и квисцинсульфгидрилоксидаза 1), которые показали наибольшую статистическую значимость и площадь под ROC кривой [8].…”
Section: ключевые моменты Key Messagesunclassified